Seasonality and shift in age-specific malaria prevalence and incidence in Binko and Carrière villages close to the lake in Selingué, Mali. (December 2016) - Touré, Mahamoudou; Sanogo, Daouda; Dembele, Soumaila; Diawara, Sory; Oppfeldt, Karen; Schiøler, Karin; Haidara, Dade; Traoré, Sékou; Alifrangis, Michael; Konradsen, Flemming; Doumbia, Seydou
Abstract Background Malaria transmission in Mali is seasonal and peaks at the end of the rainy season in October. This study assessed the seasonal variations in the epidemiology of malaria among children under 10 years of age living in two villages in Selingué: Carrière, located along the Sankarani River but distant from the hydroelectric dam, and Binko, near irrigated rice fields, close to the dam. The aim of this study was to provide baseline data, seasonal pattern and age distribution of malaria incidence in two sites situated close to a lake in Selingué. Methods Geographically, Selingué area is located in the basin of Sakanrani and belongs to the district of Yanfolila in the third administrative region of Mali, Sikasso. Two cross-sectional surveys were conducted in October 2010 (end of transmission season) and in July 2011 (beginning of transmission season) to determine the point prevalence of asymptomatic parasitaemia, and anaemia among the children. Cumulative incidence of malaria per month was determined in a cohort of 549 children through active and passive case detection from November 2010 through October 2011. The number of clinical episodes per year was determined among the children in the cohort. Logistic regression was used to determine risk factors for malaria. Results The prevalence of malaria parasitaemia varied significantly between villages with a strong seasonality in Carrière (52.0–18.9 % in October 2010 and July 2011, respectively) compared with Binko (29.8–23.8 % in October 2010 and July 2011, respectively). Children 6–9 years old were at least twice more likely to carry parasites than children up to 5 years old. For malaria incidence, 64.8–71.9 % of all children experienced at least one episode of clinical malaria in Binko and Carrière, respectively. The peak incidence was observed between August and October (end of the rainy season), but the incidence remained high until December. Surprisingly, the risk of clinical malaria was two- to nine-fold higher among children 5–9 years old compared to younger children. Conclusions A shift in the peak of clinical episodes from children under 5–9 years of age calls for expanding control interventions, such as seasonal malaria chemoprophylaxis targeting the peak transmission months.